Protection of Traditional Cloth Tapis Lampung in Communal Intellectual Property Rights Regime - Yunita Maya Putri; Ria Wierma Putri; Rehulina Rehulina (Faculty of Law, Maranatha Christian University, 2022)
Lampung Province has a Traditional Cultural Expressions (TCE) heritage in the form of cloth “Tapis